Preparação de sílicas organofuncionalizadas para imobilização da lipase de Burkholderia capacia - Silva, André Leonardo Patrício (2012)
The preparation of stable immobilized lipases is one of the great challenges for modern biotechnology that involves the use of these enzymes in biocatalyzed processes. The commercial application of these biocatalysts depends of an efficient immobilization and the appropriate use of supports to ensure stability to enzymes. This work focused on the study of the preparation of chemically modified supports derived from silica gel. The organofunctionalized silicas were prepared by silylation through of the heteregeneous route using the compounds 3-aminepropyl- and 3-chloropropyl trimethoxysilane resulting in the solids named Sil-propil-NH2 and Sil-propil-Cl, respectively. The solids Sil-propil-NH2 and Sil-propil-Cl reacted subsequently with the cyanuric chloride and 1,6 diaminehexane as spacer, followed by covalent attack of cyanuric chloride resulting in the matrices Sil-propil-N-CC and Sil-propil-Hex-CC. Silica gel and the modified solid were characterized measures of adsorption / desorption of nitrogen, CHN elemental analysis, thermogravimetry (TG), Si29 and C13 NMR and FTIR spectroscopy. The modified support were used in the immobilization of the Burkholderia cepacia lipase, and the catalytic performance and stability of the immobilized enzyme derivatives were investigated in the hydrolysis reaction of p-nitrophenylpalmitate (pNPP) in five consecutive reaction cycles. The results of the preparation of matrizes showed the anchoring of the triazine molecule onto silanized surface. For material Sil-propil-N-CC was observed the increasing of the nitrogen content as indicated CNH elemental analysis, that corresponded to 1.82% of N due the introduction of amino group and 3.08% of N after the reaction of the triazine molecule. For the material Sil-propil-Cl, it was observed the increasing in the nitrogen percentage for the support with spacer (2.13% of N) and after the reaction with cyanuric chloride (3.6% of N). The tests of catalytic activity operational stability of the immobilized enzymes onto supports were 2910, 3000 e 3430 U/g, respectively, for supports with aminopropyl and triazine molecule, chloropropyl with the spacer and for the surface with spacer and triazine molecule. For catalytic test were observed a higher tendency for loss of stability for support without spacer. The obtained results showed that the chemical modification reactions of silica gel enabled the covalent anchoring of the cyanuric chloride and the use of spacer resulted in higher catalytic activity and stability for the immobilized bio catalysts.